2008
DOI: 10.1111/j.1471-0528.2007.01652.x
|View full text |Cite
|
Sign up to set email alerts
|

Crocus sativus L. (saffron) in the treatment of premenstrual syndrome: a double‐blind, randomised and placebo‐controlled trial

Abstract: Objective The aim of this double-blind and placebo-controlled trial was to investigate whether saffron (stigma of Crocus sativus L.) could relieve symptoms of premenstrual syndrome (PMS).Design Double-blind, randomised and placebo-controlled trial.Setting Departments of Gynaecology/Obstetrics and Psychiatry, Tehran and Zanjan University of Medical Sciences.Population Women aged 20-45 years with regular menstrual cycles and experience of PMS symptoms for at least 6 months were eligible for the study.Method Wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(101 citation statements)
references
References 21 publications
2
93
0
3
Order By: Relevance
“…[26][27][28][29] Recent studies have shown the beneficial effects of saffron in depression, premenstrual syndrome and Alzheimer's disease. [30][31][32][33] …”
Section: Historymentioning
confidence: 99%
“…[26][27][28][29] Recent studies have shown the beneficial effects of saffron in depression, premenstrual syndrome and Alzheimer's disease. [30][31][32][33] …”
Section: Historymentioning
confidence: 99%
“…Jujube fruit contains flavonoids along with sterols, tannins, and saponins (5). Saffron (Crocus sativus) is a small herb belonging to the Iridaceae family (6). The extract of this plant contains alpha crocetin, water-soluble carotenoids, crocins, and safranal (7).…”
Section: Introductionmentioning
confidence: 99%
“…176 The evidence-based reviews concluded that RCTs have not suggested consistent benefit for Ginkgo biloba, evening primrose oil and homeopathic treatments but that initial positive RCTs suggest further study of massage, 177 reflexology, 178 chiropractic manipulation 179 and biofeedback. 180 Small RCTs have reported that saffron 181 and Qi therapy 182 were each superior to placebo in women with prospectively confirmed PMS. There have been positive open reports, but no RCTs, with Hypericum, 183,184 yoga, 185 guided imagery, 186 photic stimulation 187 and acupuncture.…”
Section: Herbal Complementary and Other Treatmentsmentioning
confidence: 99%